The rose and the beast : fairy tales retold - Block, Francesca Lia. (New York : Joanna Cotler Books/HarperCollins, 2000)
Nine classic fairy tales set in modern, magical landscapes and retold with a twist.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Fairy tales; Short stories; Fairy tales; Short stories